Extent of lymph node dissection at nephrectomy affects cancer‐specific survival and metastatic progression in specific sub‐categories of patients with renal cell carcinoma (RCC). (22nd May 2014) - Capitanio, Umberto; Suardi, Nazareno; Matloob, Rayan; Roscigno, Marco; Abdollah, Firas; Di Trapani, Ettore; Moschini, Marco; Gallina, Andrea; Salonia, Andrea; Briganti, Alberto; Montorsi, Francesco; Bertini, Roberto
<x xml:space="preserve">Abstract</x> Objective To test whether the number of lymph nodes removed affects cancer‐specific survival (CSS) or metastatic progression‐free survival (MPFS) in different renal cell carcinoma (RCC) scenarios. Methods We used Cox regression analyses to analyse the effect of the number of lymph nodes removed on CSS and MPFS in 1983 patients with RCC treated with nephrectomy. To adjust for possible clinical and surgical selection bias, analyses were further adjusted for number of positive nodes, presence of metastases, age, performance status, T stage, tumour size and grade. Results The prevalence of lymph node invasion was 6.1%. The mean follow‐up period was 83.3 months. Multivariable analyses showed that the number of nodes removed had an independent, protective effect on CSS in patients with pT2a–pT2b or pT3c–pT4 RCC (hazard ratio [HR] 0.91, P = 0.008 and HR 0.89, P < 0.001, respectively), in patients with bulky tumours (tumour size >10 cm, HR 0.97, P = 0.03) or when sarcomatoid features were found (HR 0.81, P = 0.006). The removal of each additional lymph node was associated with a 3–19% increase in CSS. When considering MPFS as an endpoint, the number of nodes removed had an independent, protective effect in the same patient categories. Conclusions When clinically indicated, the number of nodes removed affects CSS and MPFS in specific sub‐categories of patients with RCC.